Decolorization of methylene blue by Ag/SrSnO3 composites under ultraviolet radiation - Junploy P. (Hindawi Publishing Corporation, 2014)
SrSn(OH)6 precursors synthesized by a cyclic microwave radiation (CMR) process were calcined at 900°C for 3 h to form rod-like SrSnO 3. Further, the rod-like SrSnO3 and AgNO3 in ethylene glycol (EG) were ultrasonically vibrated to form rod-like Ag/SrSnO 3 composites, characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), electron microscopy (EM), Fourier transform infrared (FTIR) spectroscopy, and UV-visible analysis. The photocatalyses of rod-like SrSnO3, 1 wt%, 5 wt%, and 10 wt% Ag/SrSnO3 composites were studied for degradation of methylene blue (MB, C 16H18N3SCl) dye under ultraviolet (UV) radiation. In this research, the 5 wt% Ag/SrSnO3 composites showed the highest activity, enhanced by the electron-hole separation process. The photoactivity became lower by the excessive Ag nanoparticles due to the negative effect caused by reduction in the absorption of UV radiation. © 2014 Patcharanan Junploy et al.